Phenolic compounds of Bassia prostrata (Chenopodiaceae) - Petruk Anastasia (EDP Sciences, 2021)
The composition and content of phenolic compounds in plants of the polymorphic species Bassia prostrata (Chenopodiaceae) from geographically distant populations were studied by high-performance liquid chromatography. The material for the study was the aboveground part of the plant. The plants were collected in the flowering phase in Russia (Novosibirsk region, Republic of Tyva, Khakassia, Buryatia, Altai), Kazakhstan, Armenia. The phenolic compounds were extracted by double extraction with 70% ethanol. Component composition of the phenolic complex was investigated by Agilent 1200 chromatograph. Eleven phenolic compounds, including isoquercitrin, kaempferol-3-glycoside, isoramnetin-3-rutinoside, and luteolin were found in the composition. The quantitative content of each compound could vary from 0.1 to 10.8 mg/g in different populations. Chemotypes were determined for the qualitative and quantitative content of phenolic compounds